HuR Affects the Radiosensitivity of Esophageal Cancer by Regulating the EMT-Related Protein Snail - Hu, Yan; Li, Qing; Yi, Ke; Yang, Chi; Lei, Qingjun; Wang, Guanghui; Wang, Qianyun; Xu, Xiaohui (Frontiers in Oncology, 2022)
Purpose We previously found that Hu antigen R (HuR) can regulate the proliferation and metastasis of esophageal cancer cells. This study aims to explore the effects of HuR on the radiosensitivity of esophageal cancer. Materials and Method Analyses of CCK-8, colony formation assay, Western blot, immunofluorescence, flow cytometry, reactive oxygen species (ROS), and mitochondrial membrane potential were conducted to characterize the esophageal cancer cells. Nude mouse models were used to detect the effects of HuR in a combination of X-ray treatment on the subcutaneous xenografts of esophageal cancer. In addition, a luciferase assay was used to detect the direct interaction of HuR with Snail mRNA 3’-UTR. Results The down-regulation of HuR combined with X-ray can significantly inhibit the proliferation and colony formation of esophageal cancer cells. Flow cytometry data showed that the down-regulation of HuR could induce a G1 phase cell cycle block in esophageal cancer cells, and aggravate X-ray-induced apoptosis, indicated by the increases of apoptosis-related proteins Bax, caspase-3 and caspase-9. Moreover, the down-regulation of HuR could significantly impair the mitochondrial membrane potential and increase the ROS production and DNA double-strand break marker γH2AX expression in esophageal cancer cells that were exposed to X-rays. In vivo data showed that the down-regulation of HuR combined with radiation significantly decreased the growth of subcutaneous xenograft tumors. Furthermore, HuR could interact with Snail. Up-regulation of Snail can reverse the EMT inhibitory effects caused by HuR down-regulation, and attenuate the tumor-inhibiting and radiosensitizing effects caused by HuR down-regulation. Conclusion In summary, our data demonstrate that HuR effectively regulates the radiosensitivity of esophageal cancer, which may be achieved by stabilizing Snail. Thus, HuR/Snail axis is a potentially therapeutic target for the treatment of esophageal cancer.